Development of nanosilver-coated geopolymer beads (AgGP) from fly ash and baluko shells for antimicrobial applications - dela Cerna, KImmie S. (Animo Repository, 2018)
Geopolymers are a class of material formed from reacting alumina (Al2O3) and silica (SiO2) containing materials with an alkali activator. Upon curing, they solidify into rigid structures akin to Ordinary Portland Cement. Their superior fire and acid attack resistance as well as their sustainability make them a promising alternative to conventional construction materials, and they are most notable for being so. Recent findings show they may also have antimicrobial potential, particularly upon porosity enhancement and addition of a nanosilver coating. The increased porosity creates more available space for nanosilver attachment, which theoretically should increase antimicrobial activity. For this study, porous geopolymers were developed from fly ash and calcined Baluko or pen shells, both of which are considered as waste materials. The fly ash acts as a source of reactive SiO2 and Al2O3, while the Baluko shells accelerate setting time. The geopolymer paste was injected dropwise into a hot liquid medium. Due to surface tension effects as well as the accelerated setting time courtesy of the Baluko shells and the high temperature, the geopolymer rapidly solidifies into 3-4mm beads. The beads were then dipped in AgNO3 and NaBH4, which deposited silver ions on the geopolymer surface and then reduced these ions into nanosilver particles, forming the nanosilver coated geopolymer (AgGP). When put in water, a controlled release of silver ions leach out from the beads, neutralizing any bacteria in the water. The ratio of Baluko shell to fly ash in the raw material (BS/FA), H2O2 dosage, and concentration of AgNO3 used (MAg) were all varied to determine their effect against bacteria reduction. Results of the antimicrobial test against E. coli indicate significant antimicrobial activity of the AgGP compared to uncoated samples. Percentage bacteria reductions (%BR) between 77.6 to as high as 99.96% were obtained, starting from 105 CFU/mL E. coli (control samples had 43.53% reduction). ANOVA also suggests two-variable interaction effects between BS/FA, H2O2 dosage, and AgNO3 concentration may have significant effect on %BR.